KEBIJAKAN PENDIDIKAN PONDOK PESANTREN PASCA PENGESAHAN UU NO.18 TAHUN 2019 TENTANG PESANTREN - M. Wildan Hafidz; Titi Kadi (Laboratorium Pembelajaran Bahasa, FKIP Universitas Lampung, 2026)
This study analyzes Islamic boarding school education policies after the enactment of Law Number 18 of 2019 concerning Islamic Boarding Schools. The main issue raised is the transformation of pesantren education policies in strengthening institutional recognition, educational quality, and the role of pesantren in the national education system. The significance of this study lies in the strategic position of pesantren as indigenous Islamic educational institutions that have historically contributed to religious, social, and national development in Indonesia. This study employs a qualitative approach using a systematic literature review method on various policy documents, scientific journals, and government regulations related to pesantren education from 2019 to 2026. The findings indicate that the enactment of the Pesantren Law has strengthened the legal standing of pesantren, increased state support through funding and educational facilitation, and encouraged curriculum modernization while maintaining pesantren traditions and values. However, several challenges remain, including disparities in infrastructure, human resource quality, and administrative readiness among pesantren. The study concludes that the Pesantren Law has become a strategic foundation for strengthening Islamic boarding school education in Indonesia and supporting the development of moderate, independent, and competitive Islamic education in the era of globalization.Keywords: Religious Moderation, Radicalism, Islamic Universities, Public Policy, Wasathiyah. Penelitian ini menganalisis kebijakan pendidikan pondok pesantren pasca pengesahan Undang-Undang Nomor 18 Tahun 2019 tentang Pesantren. Permasalahan utama yang diangkat adalah transformasi kebijakan pendidikan pesantren dalam memperkuat pengakuan kelembagaan, kualitas pendidikan, serta peran pesantren dalam sistem pendidikan nasional. Signifikansi penelitian ini terletak pada posisi strategis pesantren sebagai lembaga pendidikan Islam asli Indonesia yang secara historis berkontribusi terhadap pembangunan keagamaan, sosial, dan kebangsaan. Penelitian ini menggunakan pendekatan kualitatif dengan metode systematic literature review terhadap berbagai dokumen kebijakan, jurnal ilmiah, dan regulasi pemerintah terkait pendidikan pesantren pada rentang tahun 2019 hingga 2026. Hasil penelitian menunjukkan bahwa pengesahan UU Pesantren telah memperkuat legitimasi hukum pesantren, meningkatkan dukungan negara melalui pendanaan dan fasilitasi pendidikan, serta mendorong modernisasi kurikulum tanpa menghilangkan tradisi dan nilai khas pesantren. Namun demikian, implementasi kebijakan masih menghadapi tantangan berupa kesenjangan sarana prasarana, kualitas sumber daya manusia, serta kesiapan administrasi antar pesantren. Kesimpulannya, UU Pesantren menjadi landasan strategis dalam penguatan pendidikan pondok pesantren di Indonesia sekaligus mendukung pengembangan pendidikan Islam yang moderat, mandiri, dan berdaya saing di era globalisasi.